Seasonal Variability of Thermocline, Sound Speed & Probable Shadow Zone in Sunda Strait, Indonesia - Tri Aji; Widodo Setiyo Pranowo; Gentio Harsono; Tasdik Mustika Alam (Journal Omni-Akuatika, 2017)
The Sunda Strait is an important strait connecting Karimata and Java Seas with the Indian Ocean. The Sunda Strait is one of the busiest International Sea-lane in Indonesian Archipelago (ALKI). That is used for commercial shipping lanes and possibly for the military (submarines) cruise. For submarine operational purposes, a physical oceanographic dataset is needed which consisting of temperature, salinity, and sound speed. This article is analysing the seasonal variablity of thermocline and sound speed, including a shadow zone estimation. The 0.1 deg C gradient is applied for the thermocline layer determination during four seasons data in 2014. The dataset of INDESO Project (daily, 1/12 deg) has been used. In the North-West Season (January), thermocline layer (28 - 13.5 deg C) occurs at 77 - 155 m depth, has a range of 1,542 - 1,504 m/s sound speed. Those reveals shallower (40 - 130 m depth) of the thermocline layer (29 - 15.8 deg C) during the first Transitional Season (April), with the sound speed range 1,541 - 1,511 m/s. During South-East Season (July), the thermocline layer (29 - 15.4 deg C) has been deeper again (65 - 155 m depth), with 1,542 - 1,550 m/s of sound speed. While during the Second Transitional Season (October), the upper limit of thermocline layer (27 - 13.6 deg C) is a little bit shallower (55 - 155 m depth), with the sound speed range of 1,538 - 1,504 m/s. In annual average, the thermocline (29 - 13.6 deg C) in Sunda Strait laying in between an upper limit layer of 40 - 70 m depths and a bottom limit layer of 130 - 155 m depth. Those layers depth are estimated to be a probable shadow zone area with the sound speed range upper limit of 1,542 m/s. and the lower limit of 1,504 - 1,511 m/s.